The Associations of Cerebrospinal Fluid ApoE and Biomarkers of Alzheimer’s Disease: Exploring Interactions With Sex - Liu, Ying; Song, Jing-Hui; Xu, Wei; Hou, Xiao-He; Li, Jie-Qiong; Yu, Jin-Tai; Tan, Lan; Chi, Song; , and Alzheimer’s Disease Neuroimaging Initiative (Frontiers in Neuroscience, 2021)
Background Sex-related difference in Alzheimer’s disease (AD) has been proposed, and apolipoprotein E (ApoE) isoforms have been suggested to be involved in the pathogenesis of AD. Objective We aimed to explore whether cerebrospinal fluid (CSF) ApoE is associated with AD biomarkers and whether the associations are different (between sexes). Methods Data of 309 participants [92 with normal cognition, 148 with mild cognitive impairment (MCI), and 69 with AD dementia] from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) were cross-sectionally evaluated with the multiple linear regression model and longitudinally with the multivariate linear mixed-effects model for the associations of CSF ApoE with AD biomarkers. Sex–ApoE interaction was used to estimate whether sex moderates the associations of CSF ApoE and AD biomarkers. Results Significant interactions between CSF ApoE and sex on AD biomarkers were observed [amyloid-β (Aβ): p = 0.0169 and phosphorylated-tau (p-tau): p = 0.0453]. In women, baseline CSF ApoE levels were significantly associated with baseline Aβ (p = 0.0135) and total-tau (t-tau) (p < 0.0001) as well as longitudinal changes of the biomarkers (Aβ: p = 0.0104; t-tau: p = 0.0110). In men, baseline CSF ApoE levels were only correlated with baseline p-tau (p < 0.0001) and t-tau (p < 0.0001) and did not aggravate AD biomarkers longitudinally. Conclusion The associations between CSF ApoE and AD biomarkers were sex-specific. Elevated CSF ApoE was associated with longitudinal changes of AD biomarkers in women, which indicates that CSF ApoE might be involved in the pathogenesis of AD pathology in a sex-specific way.